Prevalensi dan Determinan Gangguan Muskuloskeletal Pasca Banjir Pada Masyarakat Dewasa di Batang Toru Sumatra Utara - Sandi Akbar; Toto Marzuki; Nova Relida Samosir; Siti Muawanah (LPPM Universitas Abdurrab, 2026)
Background Floods are hydrometeorological disasters that have extensive impacts on public health; however, musculoskeletal disorders are often overlooked in post-disaster studies. Heavy physical activities, non-ergonomic postures, and prolonged exposure to extreme environments during and after floods may increase the risk of musculoskeletal disorders among adults. This study aimed to determine the prevalence and determinants of post-flood musculoskeletal disorders among adult populations in Batang Toru, North Sumatra.This study employed an analytical observational design with a cross-sectional approach. A total of 210 flood-affected adults were selected using multistage cluster random sampling. Musculoskeletal disorders were assessed using standardized questionnaires, while determinant variables included demographic characteristics, flood exposure, and physical activities during flooding. Data were analyzed using bivariate analysis and multivariate logistic regression. The results showed that the prevalence of post-flood musculoskeletal disorders was 62.4%. The most frequently affected body regions were the lower back, shoulders, and knees. Multivariate analysis revealed that age over 45 years (OR=2.18), engagement in heavy physical activities during floods (OR=2.73), and flood exposure lasting seven days or more (OR=1.96) were significant determinants of musculoskeletal disorders (p<0.05). Conclusion: Post-flood musculoskeletal disorders are relatively high and are influenced by age and physical exposure.